Cyclovirus in nasopharyngeal aspirates of Chilean children with respiratory infections - Phan, Tung Gia (Society for General Microbiology, 2014)
Some respiratory tract infections remain unexplained despite extensive testing for common pathogens. Nasopharyngeal aspirates (NPAs) from 120 Chilean infants from Santiago with acute lower respiratory tract infections were analysed by viral metagenomics, revealing the presence of nucleic acids from anelloviruses, adenovirus-associated virus and 12 known respiratory viral pathogens. A single sequence read showed translated protein similarity to cycloviruses. We used inverse PCR to amplify the complete circular ssDNA genome of a novel cyclovirus we named CyCV-ChileNPA1. Closely related variants were detected using PCR in the NPAs of three other affected children that also contained anelloviruses. This report increases the current knowledge of the genetic diversity of cycloviruses whose detection in multiple NPAs may reflect a tropism for human respiratory tissues.